2018
DOI: 10.1016/j.jim.2018.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Biomarker analysis of fucosylated kininogen through depletion of lectin reactive heterophilic antibodies in hepatocellular carcinoma

Abstract: Hepatocellular carcinoma (HCC) accounts for >700,000 deaths worldwide, largely related to poor rates of diagnosis. Our previous work identified glycoproteins with increased levels of fucosylation in HCC. Plate-based assays to measure this change were compromised by increased levels of heterophilic antibodies with glycan lacking terminal galactose residues, which allowed for increased binding to the lectins used in these assays. To address this issue, we developed a multi-step protein A/G incubation and filtrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…Yet unlike an ELISA, no secondary antibody or lectin is needed for this methodology as mass spectrometry provides sensitive and specific detection of distinct N-glycans. Antibody capture also negates the need for sample cleanup prior to MS analysis, which can be extensive. ,, As is typical for serum-based assays, evidence for the presence of heterophilic antibodies in cirrhotic serum has been observed with nonspecific binding to some antibodies assayed, which can lead to false positives in clinical assays. , However, as the heterophilic antibodies have a very distinct glycan profile, these can be accounted for in any given run and subtracted from the main spectra if required.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Yet unlike an ELISA, no secondary antibody or lectin is needed for this methodology as mass spectrometry provides sensitive and specific detection of distinct N-glycans. Antibody capture also negates the need for sample cleanup prior to MS analysis, which can be extensive. ,, As is typical for serum-based assays, evidence for the presence of heterophilic antibodies in cirrhotic serum has been observed with nonspecific binding to some antibodies assayed, which can lead to false positives in clinical assays. , However, as the heterophilic antibodies have a very distinct glycan profile, these can be accounted for in any given run and subtracted from the main spectra if required.…”
Section: Discussionmentioning
confidence: 99%
“…Each patient had a normal ultrasound; if serum AFP was elevated, a CT or MRI showed no liver mass. Further patient details regarding these samples are found in our previous publication …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, research in patients with HCC with abnormal serum AFP levels has revealed that fucosylation may not be restricted to AFP, and a previous study confirmed its presence in other proteins ( 11 ). Although the molecular mechanism of abnormal fucosylation in HCC has not been fully clarified, previous research identified multiple proteins with differential fucosylation, including the Golgi protein 73 ( 12 ), haptoglobin ( 13 ), α-1-acid glycoprotein ( 14 ) and kininogen ( 15 ), which may be used as potential markers for HCC diagnosis. However, none of these markers could be applied as widely as AFP-L3 in clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…Fucosylation has also been observed directly in the tumor itself(91) and together these results strongly suggest that increased fucosylation, both core and outer arm, occurs on a large number of proteins.Only a limited number of Phase I and Phase II studies have been conducted for the fucosylated glycoproteins. The most notable is fucosylated kininogen, which has been examined in several independent phase II cohorts (internal and external validation) (71,92,93)…”
mentioning
confidence: 99%